STAT1 signaling is not regulated by a phosphorylation-acetylation switch - Antunes, Filipa; Marg, Andreas; Vinkemeier, Uwe (American Society for Microbiology, 2011)
The treatment of cells with histone deacetylase inhibitors (HDACi) was reported to reveal the acetylation of STAT1 at lysine 410 and lysine 413 (O. H. Kra¨mer et al., Genes Dev. 20:473–485, 2006). STAT1 acetylation was proposed to regulate apoptosis by facilitating binding to NF-B and to control immune responses by suppressing STAT1 tyrosine phosphorylation, suggesting that STAT1 acetylation is a central mechanism by which histone deacetylase inhibitors ameliorate inflammatory diseases (O. H. Kra¨mer et al., Genes Dev. 23:223–235, 2009). Here, we show that the inhibition of deacetylases had no bearing on STAT1 acetylation and did not diminish STAT1 tyrosine phosphorylation. The glutamine mutation of the alleged acetylation sites, claimed to mimic acetylated STAT1, similarly did not diminish the tyrosine phosphorylation of STAT1 but precluded its DNA binding and nuclear import. The defective transcription activity of this mutant therefore cannot be attributed to STAT1 acetylation but rather to the inactivation of the STAT1 DNA binding domain and its nuclear import signal. Experiments with respective cDNAs provided by the authors of the studies mentioned above confirmed the results reported here, further questioning the validity of the previous data. We conclude that the effects and potential clinical benefits associated with histone deacetylase inhibition cannot be explained by promoting the acetylation of STAT1 at lysines 410 and 413.